Effect of Low-Temperature Storage on Diaeretiella rapae (McIntosh) (Hymenoptera: Braconidae) - Silva, R. J. [UNESP]; Cividanes, F. J. [UNESP]; Pedroso, E. C.; Barbosa, J. C. [UNESP]; Matta, D. H. [UNESP]; Correia, E. T. [UNESP]; Otuka, A. K. [UNESP] (Springer Nature, 2013)
We evaluated the effects of constant low-temperature storage on Diaeretiella rapae (McIntosh) (Braconidae, Aphidiinae). Diaeretiella rapae mummies were stored at 5 ± 1°C for 0-36 days. The percentage of D. rapae emergence varied (100-83%) after 0-32 days of storage. After 32 days, emergence reduced to 55%. According to our Probit analysis, 50% mortality (LT50) of the population of D. rapae was reached after 40 days of storage at 5°C. Storage for up to 32 days did not negatively affect emergence and survival. Cold exposure of D. rapae for 36 days did not influence morphological malformations, sex ratio, and emergence of the F1 generation. After 4-36 days of storage, D. rapae showed a gradual decrease in emergence, longevity, reproductive capacity, and F1 sex ratio. Diaeretiella rapae can be stored for up to 24 days at 5°C, at which time the percentage of parasitism and the F1 sex ratio remain above 38% and at 0.50, respectively. © 2013 Sociedade Entomológica do Brasil.
Keywords: Applied biological control; fitness attributes; parasitoids; quality control; rearing techniques